Significance of coconuts in Koli ritual - Mumbai Archive Project Team (Jio Institute, 2024)
Various farm offerings are made to the effigy of Holika, particularly coconuts, which symbolize fertility and prosperity in Koli culture. Coconuts are integral to all major Koli rituals, ranging from Narali purnima to wedding ceremonies and the Holika dahan rituals.